Remediation of sandy soils contaminated with hydrocarbons and halogenated hydrocarbons by soil vapour extraction - José Tomás Albergaria (2012)
This paper presents the study of the remediation of sandy soils containing six of the most commoncontaminants (benzene, toluene, ethylbenzene, xylene, trichloroethylene and perchloroethylene) usingsoil vapour extraction (SVE). The influence of soil water content on the process efficiency was evaluatedconsidering the soil type and the contaminant. For artificially contaminated soils with negligible claycontents and natural organic matter it was concluded that: (i) all the remediation processes presentedefficiencies above 92%; (ii) an increase of the soil water content led to a more time-consuming remediation; (iii) longer remediation periods were observed for contaminants with lower vapour pressuresand lower water solubilities due to mass transfer limitations. Based on these results an easy and relatively fast procedure was developed for the prediction of the remediation times of real soils; 83% of theremediation times were predicted with relative deviations below 14%.